Creating deeper attachments: Reflections on developing arts-based pedagogy and practice within psychology - Kitrina Douglas; David Carless (Methods in Psychology)
In this article we explore the potential of arts-based methodologies to contribute to pedagogy and practice in psychology. Drawing on insights developed by Elliot Eisner (2008) related to what education can learn from the arts, we first explore how Eisner's ideas, along with our experiences, might infuse research supervision. Through ‘applied practice’ we then identify some of the potential benefits and challenges of including arts-based methods during supervision. Reflections show how important it is to create a safe space, deconstruct hierarchies, and provide examples of arts-based research, along with an opportunity to experiment and share. Together, these seem to support the development of trusting mature relationships that can lead to personal growth and transformation. While we have become advocates for the potential of arts-based research in psychology our reflections also identify a number of challenges and conditions to realising such benefits.